Complete genome sequence of marine Roseobacter lineage member Monaibacterium sp. ALG8 with six plasmids isolated from seawater around brown algae - Sun, Cong; Fang, Yuan-Chun; Li, Hao; Chen, Jie; Ye, Yong-Lian; Ni, Ling-Fang; Xu, Lin; Han, Bing-Nan; Wu, Min; Wang, Chun-Sheng; Xu, Xue-Wei (Marine genomics, 2021)
Monaibacterium sp. ALG8 (=MCCC 1 K04733) was isolated from seawater around brown algae. The genome of Monaibacterium sp. ALG8 was sequenced, one circular 3,036,380 bp chromosome and six circular plasmids ranging from 12,229 to 151,263 bp were found after assembly. The results of genomic annotation showed that Monaibacterium sp. ALG8 lacks the ability to degrade alginate, indicating its ecological role may not be directly related to the degradation of brown algae. The comparison of genomic features in the plasmids showed that almost all of these plasmids, except pALG4, were horizontally recruited from donors, not ancestors. Based on predicted functions, the existence of plasmids may provide strain ALG8 with advantages including nitrate reduction, tolerance of osmotic stress via glycine betaine, resistance to heavy metal stress such as mercury and cobalt, degradation of benzoate metabolites such as p-cumate, transformation of the swim-or-stick lifestyle and improvement of the immune system with two CRISPR–Cas systems. This study provides evidence for the carbon metabolic patterns of Monaibacterium sp. ALG8 and predicts the functions and donors of six plasmids in this strain, broadening our understanding of the ecological roles of bacteria in the environment around brown algae and the functions and evolutionary patterns of plasmids in marine Roseobacter lineage members.